The Relationship between Knowledge and Attitude of Pulmonary TB Patients on the Prevention of Pulmonary TB Disease Transmission at Puskesmas Padangmatinggi - Rahmat Rizki Siregar; Elpiana Sari; Desi Meliana Gultom; Hakki Ahmadi (Science Midwifery, 2022)
Mycobacterium tuberculosis which is one of the lower respiratory tract diseases. This research is descriptive, the method of collecting data from interview experience using a questionnaire/questionnaire. From the results of the study of the relationship between knowledge and attitudes of pulmonary TB patients towards the prevention of transmission of pulmonary TB disease at the Padangsidimpuan Health Center in 2022. it can be concluded that of 23 respondents, the majority of respondents were 23 respondents with sufficient knowledge and did not take steps to prevent transmission as many as 11 people (73.3%) 1 person (20%). From the results of statistical tests conducted by researchers using the SPSS program, the respondents' knowledge obtained p-value = 0.009 (p < 0.05) meaning Ho was accepted and H1 was rejected, so there was a relationship between knowledge on the Prevention of Pulmonary TB Disease Transmission at the Puskesmas Padangmatinggi. The respondent's attitude variable obtained p-value = 0.317 (p > 0.05) Ho is rejected and H1 is accepted, it can be concluded that there is no relationship between patient attitudes towards the Prevention of Pulmonary TB Disease Transmission